Feast and Famine in the Operatic Historiography of the Río de la Plata (Revista Argentina de Musicología, 2020)
The intertwined histories of opera in Buenos Aires and Montevideo during the nineteenth century follow a similar pattern to that found elsewhere in Latin America: a burst of activity in the 1820s into the 1830s, in the wake of independence, followed by a yawning gap of years or decades, before a second wave of performances takes off within sight of 1850. But if such outlines seem clear enough, key historiographical questions remain: how much prominence to give to complete performances over the wide circulation of operatic excerpts, for instance; and how to push beyond national boundaries in order to understand the interrelationship of local, regional and transatlantic networks. Above all, meanwhile, how to rethink the apparent cycles of operatic scarcity and abundance that characterize the region’s early operatic history?In this article, I argue that opera’s continued presence on both sides of the Río de la Plata during the “gap years” of the 1830s and 40s can best be measured not through the very occasional complete (or near-complete) performances, but through the synecdochic ability of individual arias to stand in for entire imagined works, whose merits were argued out in the pages of contemporary newspapers as if available on stage. Meanwhile, the return of full-scale opera in both cities in the early 1850s, with twenty-nine local premieres in Montevideo in 1852 alone, and over thirty in Buenos Aires two years later, deserves a crucial place in any understanding of the formation of the operatic canon, both locally and globally.
Keywords: Rossini; Bellini; operatic canon; Buenos Aires; Montevideo